Kardiomiopati Tirotoksikosis - Tallo, Nikolaus Lizu; Sihombing, Meri Estivo (Cermin Dunia Kedokteran, 2024)
Thyrotoxicosis refers to a syndrome caused by excessive secretion of thyroid hormone (hyperthyroidism). Changes in thyroid hormone levels directly affect the occurrence of abnormal changes in the structure and/or function of the heart, leading to cardiomyopathy, and increase the risk of complications such as heart failure and life-threatening arrhythmias. Global data shows approximately 1% of thyrotoxicosis patients develop dilated cardiomyopathy, leading to severe impairment of left ventricular function and cardiogenic shock. Early diagnosis and proper management are necessary for a better outcome and prognosis.